2016
DOI: 10.1163/15730255-12341319
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Implications of ‘Fatwā Shopping’ in the Islamic Finance Industry: Problems, Perceptions and Prospects

Abstract: This article examines the occurrence and legal implications of 'fatwā shopping' in the Islamic finance industry and the need to put the proper legal mechanisms in place to regulate the phenomenon. It provides a case study of the existing legal restrictions in some jurisdictions with a centralised Sharī'ah Supervisory Board at the national level such as in Malaysia. As a preliminary review of the implications of 'fatwā shopping' in the industry, this study examines the consequential problems, current perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…In jurisdictions without a central Shariah board and a lack of standardized rulings, the Islamic finance industry has been criticized for practices such as fatwa ‐shopping and Shariah arbitrage. In “ fatwa ‐shopping” Islamic financial institutions shop for lenient rulings that provide them with the best economic outcomes (Oseni, ; Oseni, Ahmad, & Hassan, ). Meanwhile, “ Shariah arbitrage” is a stratagem used to meet the demands of contemporary customers by conforming to the form but not the substance of Shariah (El‐Gamal, ; El‐Gamal, ; Garner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In jurisdictions without a central Shariah board and a lack of standardized rulings, the Islamic finance industry has been criticized for practices such as fatwa ‐shopping and Shariah arbitrage. In “ fatwa ‐shopping” Islamic financial institutions shop for lenient rulings that provide them with the best economic outcomes (Oseni, ; Oseni, Ahmad, & Hassan, ). Meanwhile, “ Shariah arbitrage” is a stratagem used to meet the demands of contemporary customers by conforming to the form but not the substance of Shariah (El‐Gamal, ; El‐Gamal, ; Garner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Islamic financial institutions shop for lenient rulings that provide them with the best economic outcomes (Oseni, 2017;Oseni, Ahmad, & Hassan, 2016). Meanwhile, "Shariah arbitrage" is a stratagem used to meet the demands of contemporary customers by conforming to the form but not the substance of Shariah (El-Gamal, 2006;El-Gamal, 2007;Garner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently two predominant types of regulatory regimes governing Shari'ah-compliant institutions in Muslim countries. One approach 111 Oseni, Umar A., Ahmad, Abu Umar Faruq, and Hassan, M. Kabir. 2016.…”
Section: Legal Impediments Regulatory Confusion and Lack Of Oversightmentioning
confidence: 99%
“…These differences which often relate to the nature of the products and services developed and endorsed by Sharī'ah scholars has been the main factor that triggered the malignant form of Fatwā shopping. In Oseni et al (2016), the different dimensions of the malignant form of Fatwā shopping identified through practices in the industry were analysed. These dimensions, though not exhaustive, include the following: proactive search, careless online search, negligent adoption of previous Fatwā, overbearing influence of some bank executives, geo-jurisprudential divergence on some Islamic finance products and appointment of 'favourable' Sharī'ah scholars.…”
Section: Effective Consumer Protection Regulationsmentioning
confidence: 99%
“…He further revealed that he had witnessed a number of instances where it happened. This was made public at the 2 nd Internal Conference on Islamic Economics & Economies of the OIC Countries, Parallel Session 3, Prince Hotel and Residence, Kuala Lumpur, January 30, 2013 (Oseni et al, 2016).…”
Section: Effective Consumer Protection Regulationsmentioning
confidence: 99%